All-solid waste recycled concrete material and preparation method thereof
By using the combination of reinforced regenerated fine aggregate, reinforced regenerated coarse aggregate and fully solid waste-based gelling materials in all solid waste regenerated concrete materials, the problems of short set time and great brittleness in premixed concrete are solved, and the mechanical properties of the material are improved and the set time is extended, which is suitable for engineering applications.
Patent Information
- Application Number
- CN202411516647.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-11
AI Technical Summary
When used in premixed concrete, the existing geopolymer gelling materials have short set time and high brittleness, making it difficult to meet the requirements of engineering applications.
All solid waste recycled concrete materials are used, which include reinforced recycled fine aggregates, reinforced recycled coarse aggregates and all solid waste-based gelling materials. Through the strengthening treatment of sodium hydroxide and sodium silicate solutions, as well as the toughening and delaying settling time of carbon oxide nanotubes and polyacrylamide, they form all solid waste-based gelling materials with enhanced toughening function.
It significantly improves the mechanical properties and performance stability of all solid waste recycled concrete materials, extends the settling time, reduces brittleness, improves the utilization rate of solid waste resource utilization, and simplifies the production process.
Smart Images

Figure BDA0005106889730000061 
Figure BDA0005106889730000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to a full-solid waste recycled concrete material and a preparation method thereof. Background Art
[0002] With the development of industrialization and urbanization in my country, a large number of old buildings have been demolished, resulting in a large amount of waste concrete, which has seriously polluted the environment. At the same time, the rapid development of my country's infrastructure has led to a shortage of resources due to excessive demand for raw materials such as natural sand and gravel. The preparation of waste concrete into recycled aggregate and its use as concrete raw materials can not only solve the problem of waste concrete treatment, but also save a lot of natural resources and achieve sustainable development of resources and environment. However, compared with natural aggregates, the surface of recycled aggregates is attached with old mortar, which has the physical properties of high water absorption, high pressure crushing value, high porosity and low density, and there are multiple interface transition zones inside the recycled concrete prepared by it, resulting in poor performance of the newly mixed recycled aggregate concrete and poor stability of performance, which makes it difficult to achieve widespread application in engineering. In addition, the carbon emission of cement production is high, and the development of low-carbon cementitious materials is urgent. It is a hot topic to replace cement with industrial solid waste geopolymer as cementitious materials. However, the setting time of geopolymer cementitious materials is short and the brittleness is large, which makes it difficult to be used in ready-mixed concrete. Summary of the invention
[0003] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a fully solid waste recycled concrete material and a preparation method thereof, so as to solve the problems in the prior art that the existing geopolymer cementitious materials have a short setting time and are very brittle, making them difficult to use in ready-mixed concrete.
[0004] To achieve the above-mentioned purpose, the first aspect of the present invention adopts the following technical solution: a fully solid waste recycled concrete material, calculated by mass fraction, includes:
[0005] Strengthen recycled fine aggregate 85-95 parts;
[0006] Strengthen recycled coarse aggregate 95-105 parts;
[0007] 25-35 parts of all-solid waste-based cementitious materials;
[0008] 16-20 parts water;
[0009] Admixture 0.5-0.7 parts;
[0010] The all-solid waste-based cementitious material includes, by mass percentage, 40%-60% slag, 10%-20% fly ash, 10%-20% old mortar powder, 10%-20% desulfurized gypsum, 0.1%-0.3% oxidized carbon nanotubes and 0.01%-0.03% polyacrylamide.
[0011] Furthermore, the reinforced recycled fine aggregate is obtained by subjecting the recycled fine aggregate to a reinforcing treatment with a sodium hydroxide solution.
[0012] Furthermore, the mass ratio of sodium hydroxide in the sodium hydroxide solution is 40%.
[0013] Furthermore, the particle size of the recycled fine aggregate is 0.16-4.75 mm.
[0014] Furthermore, the reinforced recycled coarse aggregate is obtained by mixing the recycled coarse aggregate with slag fly ash slurry, drying the mixture, and then subjecting the mixture to a reinforcing treatment with a sodium silicate solution.
[0015] Furthermore, the water-to-binder ratio of the slag fly ash slurry is 0.5, and the mass ratio of slag to fly ash is 1-3:1, and the particle sizes of the slag and fly ash are both less than 10 microns.
[0016] Furthermore, the modulus of the sodium silicate solution is 1.0-2.0.
[0017] Furthermore, the particle size of the recycled coarse aggregate is 4.75 to 19.00 mm.
[0018] Furthermore, the all-solid waste-based cementitious material is a powder with a particle size of less than 10 microns.
[0019] The second aspect of the present invention adopts the following technical solution: According to the method for preparing a fully solid waste recycled concrete material according to the first aspect of the present invention, the method comprises the following steps:
[0020] Crushing recycled waste concrete to form old mortar powder, recycled fine aggregate and recycled coarse aggregate;
[0021] The recycled fine aggregate is soaked in a sodium hydroxide solution for 2-4 hours and then dried to form a reinforced recycled fine aggregate;
[0022] Apply a layer of slag fly ash slurry on the recycled coarse aggregate, dry it, soak it in sodium silicate solution for 2-4 hours and then dry it to form reinforced recycled coarse aggregate;
[0023] Slag, fly ash, old mortar powder, desulfurized gypsum, oxidized carbon nanotubes and polyacrylamide are mixed, ground into powder, and then dried to obtain a fully solid waste-based cementitious material;
[0024] The reinforced recycled fine aggregate, the reinforced recycled coarse aggregate, the all-solid waste-based cementitious material, water and admixtures are evenly mixed to form the all-solid waste recycled concrete material.
[0025] Technical principle:
[0026] Firstly, the recycled fine aggregate and recycled coarse aggregate are strengthened. Since the main component of the recycled fine aggregate is old mortar, which contains unhydrated cementitious materials, the immersion of the alkali activator can promote the hydration of the unhydrated cementitious materials and improve the strength of the recycled fine aggregate. For the coarse aggregate, cracks are present in the recycled coarse aggregate due to crushing. The surface of the recycled coarse aggregate is wrapped with mineral powder fly ash mortar, which is allowed to penetrate into the cracks of the recycled coarse aggregate. Then, the old and new mortar on the surface are stimulated with an alkali activator to improve the strength of the recycled coarse aggregate. For the all-solid waste-based cementitious materials, the synergistic excitation between industrial solid waste and old mortar powder is used to form an all-solid waste-based cementitious materials with enhanced and toughening functions under the toughening effect of oxidized carbon nanotubes. At the same time, the setting time is delayed under the action of polyacrylamide, and the comprehensive performance of the mortar is improved. Then, the strengthened recycled fine aggregate and recycled coarse aggregate, the all-solid waste-based cementitious materials, water and admixtures are mixed to prepare an all-solid waste recycled concrete material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The reinforced recycled fine aggregate and the reinforced recycled coarse aggregate in the present invention can significantly improve the mechanical properties and performance stability of all-solid waste recycled concrete materials; the use of all-solid waste-based cementitious materials with enhanced toughness and long setting time can improve the brittleness and setting time of all-solid waste recycled concrete materials;
[0029] 2. The present invention uses all solid waste to prepare all solid waste recycled concrete materials, which can reduce the cost of concrete and improve the resource utilization rate of solid waste;
[0030] 3. The production process is simple, the operation and control are convenient, and continuous production is possible. It has strong industrialization capabilities and broad market prospects. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below through specific embodiments:
[0032] Example 1
[0033] Step 1: Recycle the waste concrete from the construction project and crush it into old mortar powder with a particle size of 0-0.075mm, recycled fine aggregate with a particle size of 0.16-4.75mm and recycled coarse aggregate with a particle size of 4.75-19.00mm;
[0034] Step 2: Soak the recycled fine aggregate in a 40% sodium hydroxide solution for 2 hours and then dry it to form a reinforced recycled fine aggregate A;
[0035] Step 3: Apply a layer of slag fly ash slurry with a water-binder ratio of 0.5 and a slag to fly ash mass ratio of 1:1 on the recycled coarse aggregate. After drying, soak it in a sodium silicate solution with a modulus of 1.5 for 4 hours and then dry it to form the reinforced recycled aggregate B.
[0036] Step 4: 40% slag, 20% fly ash, 20% old mortar powder, 19.87% desulfurized gypsum, 0.1% oxidized carbon nanotubes, and 0.03% polyacrylamide are mixed in a mass ratio, ground into powder with a particle size of less than 10 microns, and dried and stored to obtain a fully solid waste-based cementitious material C;
[0037] Step 5: Pour 90 parts of recycled fine aggregate A, 100 parts of recycled aggregate B, 30 parts of all-solid waste-based cementitious material C, 18 parts of water, and 0.6 parts of polycarboxylate water reducer into a mixer and mix to form all-solid waste recycled concrete D.
[0038] Then the initial setting time was tested, and the specimen was cast in a 100mm×100mm×100mm mold and placed in a standard curing room with the temperature and humidity set at 20°C and 95% respectively for curing for 24 hours before demolding. The specimen was then returned to the standard curing room for continued curing for 28 days, and the flexural strength and compressive strength of the specimen were tested.
[0039] Example 2
[0040] Step 1: Recycle the waste concrete from the construction project and crush it into old mortar powder with a particle size of 0-0.075mm, recycled fine aggregate with a particle size of 0.16-4.75mm and recycled coarse aggregate with a particle size of 4.75-19.00mm;
[0041] Step 2: Soak the recycled fine aggregate in a 40% sodium hydroxide solution for 4 hours and then dry it to form a reinforced recycled fine aggregate A;
[0042] Step 3: Apply a layer of slag fly ash slurry with a water-binder ratio of 0.5 and a slag to fly ash mass ratio of 2:1 on the recycled coarse aggregate. After drying, soak it in a sodium silicate solution with a modulus of 2.0 for 2 hours and then dry it to form the reinforced recycled aggregate B.
[0043] Step 4: 60% slag, 10% fly ash, 19.69% old mortar powder, 10% desulfurized gypsum, 0.3% oxidized carbon nanotubes, and 0.01% polyacrylamide are mixed in a mass ratio, ground into powder with a particle size of less than 10 microns, and dried and stored to obtain a fully solid waste-based cementitious material C;
[0044] Step 5: Pour 85 parts of recycled fine aggregate A, 95 parts of recycled aggregate B, 25 parts of all-solid waste-based cementitious material C, 16 parts of water, and 0.5 parts of polycarboxylate water reducer into a mixer and mix to form all-solid waste recycled concrete D.
[0045] Then the initial setting time was tested, and the specimen was cast in a 100mm×100mm×100mm mold and placed in a standard curing room with the temperature and humidity set at 20°C and 95% respectively for curing for 24 hours before demolding. The specimen was then returned to the standard curing room for continued curing for 28 days, and the flexural strength and compressive strength of the specimen were tested.
[0046] Example 3
[0047] Step 1: Recycle the waste concrete from the construction project and crush it into old mortar powder with a particle size of 0-0.075mm, recycled fine aggregate with a particle size of 0.16-4.75mm and recycled coarse aggregate with a particle size of 4.75-19.00mm;
[0048] Step 2: Soak the recycled fine aggregate in a 40% sodium hydroxide solution for 3 hours and then dry it to form a reinforced recycled fine aggregate A;
[0049] Step 3: Apply a layer of slag fly ash slurry with a water-binder ratio of 0.5 and a slag to fly ash mass ratio of 3:1 on the recycled coarse aggregate. After drying, soak it in a sodium silicate solution with a modulus of 1.0 for 3 hours and then dry it to form the reinforced recycled aggregate B.
[0050] Step 4: 55% slag, 15% fly ash, 14.78% old mortar powder, 15% desulfurized gypsum, 0.2% oxidized carbon nanotubes, and 0.02% polyacrylamide are mixed in a mass ratio, ground into powder with a particle size of less than 10 microns, and dried and stored to obtain a fully solid waste-based cementitious material C;
[0051] Step 5: Pour 95 parts of recycled fine aggregate A, 105 parts of recycled aggregate B, 35 parts of all-solid waste-based cementitious material C, 20 parts of water, and 0.7 parts of polycarboxylate water reducer into a mixer and mix to form all-solid waste recycled concrete D.
[0052] Then the initial setting time was tested, and the specimen was cast in a 100mm×100mm×100mm mold and placed in a standard curing room with the temperature and humidity set at 20°C and 95% respectively for curing for 24 hours before demolding. The specimen was then returned to the standard curing room for continued curing for 28 days, and the flexural strength and compressive strength of the specimen were tested.
[0053] Comparative Example 1
[0054] Step 1: Recycle the waste concrete from the construction project and crush it into old mortar powder with a particle size of 0-0.075mm, recycled fine aggregate with a particle size of 0.16-4.75mm and recycled coarse aggregate with a particle size of 4.75-19.00mm;
[0055] Step 2: 40% slag, 20% fly ash, 20% old mortar powder, 19.87% desulfurized gypsum, 0.1% oxidized carbon nanotubes, and 0.03% polyacrylamide are mixed in a mass ratio, ground into powder with a particle size of less than 10 microns, and dried and stored to obtain a fully solid waste-based cementitious material;
[0056] Step 3: Pour 90 parts of recycled fine aggregate, 100 parts of recycled coarse aggregate, 30 parts of all-solid waste-based cementitious materials, 18 parts of water and 0.6 parts of polycarboxylate water reducer into a mixer and mix to form all-solid waste recycled concrete.
[0057] Then the initial setting time was tested, and the specimen was cast in a 100mm×100mm×100mm mold and placed in a standard curing room with the temperature and humidity set at 20°C and 95% respectively for curing for 24 hours before demolding. The specimen was then returned to the standard curing room for continued curing for 28 days, and the flexural strength and compressive strength of the specimen were tested.
[0058] Comparative Example 2
[0059] Step 1: Recycle the waste concrete from the construction project and crush it into old mortar powder with a particle size of 0-0.075mm, recycled fine aggregate with a particle size of 0.16-4.75mm and recycled coarse aggregate with a particle size of 4.75-19.00mm;
[0060] Step 2: Mix 40% slag, 20% fly ash, 20% old mortar powder, 19.87% desulfurized gypsum, and 0.13% polyacrylamide in a mass ratio, grind into powder with a particle size of less than 10 microns, dry and store, and obtain a fully solid waste-based cementitious material;
[0061] Step 3: Pour 90 parts of recycled fine aggregate, 100 parts of recycled coarse aggregate, 30 parts of all-solid waste-based cementitious materials, 18 parts of water and 0.6 parts of polycarboxylate water reducer into a mixer and mix to form all-solid waste recycled concrete.
[0062] Then the initial setting time was tested, and the specimen was cast in a 100mm×100mm×100mm mold and placed in a standard curing room with the temperature and humidity set at 20°C and 95% respectively for curing for 24 hours before demolding. The specimen was then returned to the standard curing room for continued curing for 28 days, and the flexural strength and compressive strength of the specimen were tested.
[0063] Comparative Example 3
[0064] Step 1: Recycle the waste concrete from the construction project and crush it into old mortar powder with a particle size of 0-0.075mm, recycled fine aggregate with a particle size of 0.16-4.75mm and recycled coarse aggregate with a particle size of 4.75-19.00mm;
[0065] Step 2: 40% slag, 20% fly ash, 20% old mortar powder, 19.87% desulfurized gypsum, and 0.13% oxidized carbon nanotubes are mixed in a mass ratio, ground into powder with a particle size of less than 10 microns, and dried and stored to obtain a fully solid waste-based cementitious material;
[0066] Step 3: Pour 90 parts of recycled fine aggregate, 100 parts of recycled coarse aggregate, 30 parts of all-solid waste-based cementitious materials, 18 parts of water and 0.6 parts of polycarboxylate water reducer into a mixer and mix to form all-solid waste recycled concrete.
[0067] Then the initial setting time was tested, and the specimen was cast in a 100mm×100mm×100mm mold and placed in a standard curing room with the temperature and humidity set at 20°C and 95% respectively for curing for 24 hours before demolding. The specimen was then returned to the standard curing room for continued curing for 28 days, and the flexural strength and compressive strength of the specimen were tested.
[0068] The test results of the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3 are as follows:
[0069]
[0070]
[0071] From the data in the above table, it can be analyzed that: by strengthening the recycled fine aggregate and recycled coarse aggregate, and at the same time, by combining oxidized carbon nanotubes and polyacrylamide in the all-solid waste-based cementitious materials, the flexural strength and compressive strength can be enhanced, and the waste concrete can be effectively applied.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A fully solid waste recycled concrete material, characterized in that: Calculated by mass: Strengthen recycled fine aggregate 85-95 parts; Strengthen recycled coarse aggregate 95-105 parts; 25-35 parts of all-solid waste-based cementitious materials; 16-20 parts water; Admixture 0.5-0.7 parts; The all-solid waste-based cementitious material includes, by mass percentage, 40%-60% slag, 10%-20% fly ash, 10%-20% old mortar powder, 10%-20% desulfurized gypsum, 0.1%-0.3% oxidized carbon nanotubes and 0.01%-0.03% polyacrylamide.
2. The all-solid waste recycled concrete material according to claim 1, characterized in that: The reinforced recycled fine aggregate is obtained by subjecting the recycled fine aggregate to a reinforcing treatment with a sodium hydroxide solution.
3. The all-solid waste recycled concrete material according to claim 2, characterized in that: The mass proportion of sodium hydroxide in the sodium hydroxide solution is 40%.
4. The all-solid waste recycled concrete material according to claim 2, characterized in that: The particle size of the recycled fine aggregate is 0.16-4.75 mm.
5. The all-solid waste recycled concrete material according to claim 1, characterized in that: The reinforced recycled coarse aggregate is obtained by mixing recycled coarse aggregate with slag fly ash slurry, drying it, and then subjecting it to a strengthening treatment with a sodium silicate solution.
6. The all-solid waste recycled concrete material according to claim 5, characterized in that: The water-to-binder ratio of the slag-fly ash slurry is 0.5, and the mass ratio of slag to fly ash is 1-3:1, and the particle sizes of the slag and fly ash are both less than 10 microns.
7. The all-solid waste recycled concrete material according to claim 5, characterized in that: The modulus of the sodium silicate solution is 1.0-2.
0.
8. The all-solid waste recycled concrete material according to claim 5, characterized in that: The particle size of the recycled coarse aggregate is 4.75-19.00 mm.
9. The all-solid waste recycled concrete material according to claim 1, characterized in that: The all-solid waste-based cementitious material is a powder with a particle size less than 10 microns.
10. A method for preparing all-solid waste recycled concrete material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Crushing recycled waste concrete to form old mortar powder, recycled fine aggregate and recycled coarse aggregate; The recycled fine aggregate is soaked in a sodium hydroxide solution for 2-4 hours and then dried to form a reinforced recycled fine aggregate; Apply a layer of slag fly ash slurry on the recycled coarse aggregate, dry it, soak it in sodium silicate solution for 2-4 hours and then dry it to form reinforced recycled coarse aggregate; Slag, fly ash, old mortar powder, desulfurized gypsum, oxidized carbon nanotubes and polyacrylamide are mixed, ground into powder, and then dried to obtain a fully solid waste-based cementitious material; The reinforced recycled fine aggregate, the reinforced recycled coarse aggregate, the all-solid waste-based cementitious material, water and admixtures are evenly mixed to form the all-solid waste recycled concrete material.